Student’s attitudes about educational integration in the inclusive schools for people with special needs (A field study in the city of Latakia) - Charrouf, Ansab; Hasan, Nisren (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The goal of current research is to know the ordinary students in the inclusive schools attitudes towards educational integration of people with special needs, and the aim of the research is also to know the differences in these attitudes according to the variables of gender and inclusive schools. The research sample was (329) male and female pupils of the inclusive of the three schools in the city of Latakia, where the number of the original members of the society according to the Department of Education statistics for 2015 (2996). To reach the objectives of the research a measure of attitudes was adopted of ordinary students prepared by the researcher. The results confirmed that the presence of positive attitudes among students in ordinary schools merging towards educational integration, and there was no impact to the variable of type on these trends, and the results showed the existence of differences between the attitudes of students, according to school merging variable.